PENGEMBANGAN INSTRUMEN EVALUASI PROFIL SISWA PANCASILA ASPEK KEBHINEKAAN GLOBAL DAN GOTONG ROYONG PADA SISWA SEKOLAH DASAR - Ni Gusti Kadek Ristya Desiyani; I Gede Astawan; Gusti Ayu Putu Sukma Trisna (Journal of Innovation Research and Knowledge, 2024)
This research aims to produce an instrument for assessing aspects of global diversity and mutual cooperation that is valid and reliable. Retnawati's type of development research consists of 9 stages. The research subject is the evaluation instrument. The development objects are content validity, item validity and instrument reliability. The data collection method uses non-tests in the form of questionnaires. The data analysis method uses qualitative and quantitative analysis. Based on the test results, 20 questions for each aspect tested were all valid in the very high category. The test reliability results were 0.87 for the global diversity aspect instrument and 0.88 for the mutual cooperation aspect. Based on the test results, it can be concluded that the evaluation instrument for aspects of global diversity and mutual cooperation in elementary schools is in the very good category and can be used in the evaluation process. The implication of this research is that teachers can be more effective in identifying and developing awareness and appreciation of the values ​​of global diversity and mutual cooperation among students